Role of Ayurvedic Therapies in Chronic Kidney Disease Management: A Case Study on Integrating Traditional Healing (Academia Journal of Medicine, 2025)
Chronic Kidney Disease (CKD) is a progressive condition characterized by the gradual decline of kidney function, often resulting in end-stage kidney disease (ESKD), which necessitates kidney replacement therapy. While conventional treatments focus on managing these risk factors, Ayurvedic interventions have gained attention due to their holistic, individualized approach, which aims to restore balance within the body and improve kidney function. This case study evaluates the impact of Ayurvedic interventions combined with conventional treatments in a 56-year-old male patient with CKD, hypertension, and Type 2 Diabetes Mellitus (T2DM) who visited Jeena Sikho Lifecare Limited Hospital in Derabassi, Punjab. The patient presented with symptoms including general weakness, lower back ache, itching, and frothy urine. After a course of Ayurvedic treatment, significant improvements were noted in kidney function, including a reduction in serum urea and creatinine levels, as well as an increase in GFR. The patient’s symptoms, including general weakness and itching, improved markedly, and his weight decreased. The results indicate that Ayurvedic therapies, such as Ayurvedic formulations and detoxification practices, could play a supportive role in managing CKD by improving renal function and alleviating symptoms. This study highlights the potential of combining traditional Ayurvedic treatments with conventional treatment in managing CKD. However, further research with larger sample sizes and controlled clinical trials is required to establish the effectiveness of Ayurvedic approaches in CKD management and integrate them into mainstream healthcare.
Keywords: Chronic Kidney Disease (CKD); Glomerular Filtration Rate (GFR); Ayurveda; Panchakarma; Hypertension; Type II Diabetes Mellitus (T2DM); Vrikka Vikar; Vataj pandu